Energy-Exergy analysis and carbon emission of Nigerian cement manufacturing industry (2009)
Two of the largest cement manufacturing plants in Nigeria, named Plants A and B, were studied and the data collected for the 10 year period 1995- 2005 from them enabled an analysis of their energy consumption, energy cost per tonne, efficiency of energy use from exergy analysis, and carbon dioxide emission rates. The two plants account for over 70% of total local cement production in Nigeria. Both plants utilize thermal and electrical energy. With both plants having thermal to electrical energy utilization ratio of 90:10 compared to the 70:30 recommended best global practice. The Input-Output Analysis methodology was used to evaluate the embodied energy intensity which was found to increase over the period in both plants, with Plant A having the highest increase from 7.1 to 9.4 GJ/tonne. The embodied energy intensity for both plants was 50% higher than the recommended best global practice of between 2.9 and 3.2 GJ/tonne. The energy cost per tonne for both plants increased by about 1000%over the period despite a 33% reduction in total energy consumption. Efficiency of energy use evaluated from an exergy analysis in Plant A increased from 50% to 59% while in Plant B the increase was from 33%to 45% over the period, compared to the recommended global best practice of 50%. Carbon dioxide emission in both plants declined over the period, for Plant A from 765903 Tg to 548310 Tg (40%) and for Plant B from 604255 Tg to 543658 Tg (16%) over the period.